Levantamento de variáveis relevantes no estudo do autocontrole em crianças de pouca idade - Cesarino, Ana Carolina Carneiro de Lima (2011)
Based on the literature of that age would be an important variable to be considered in studies of self-control, the aim of this study was to investigate how variables such as delay and magnitude of reinforcement, the presence of the reinforcer, the presence of distractions, with the consequence contingency wait, kind of consequence and likelihood of obtaining it influenced the choice by the response of self-control in children of different ages (2 years and 4 months to 6 years and 4 months). The response of self-control is defined in this study as the delayed reinforcer and the choice of greater magnitude. In the first experimental condition manipulated the age of the children so they could observe how was the choice by the reinforcer (smaller or larger, immediate and delayed) in each age group as well as observing how children of different ages behave in the face of waiting for the reinforcer of greater magnitude. In a second experimental condition a child (2 years and 4 months to 3 years and 10 months) and an older child (4 years and 1 month to 6 years and 4 months) were placed in a condition with the dual purpose of verifying whether a children represent a model for other modifying the choice of reinforcer delivered in the first experimental condition